2008
DOI: 10.1002/hbm.20604
|View full text |Cite
|
Sign up to set email alerts
|

Parsing neural mechanisms of social and physical risk identifications

Abstract: Psychometric studies of risk perception have categorized personal risks into social and physical domains. To investigate whether and how the human brain differentiates social and physical risks, we scanned human adults using functional magnetic resonance imaging when they identified potential risks involved in social and physical behaviors. We found that the identification of risky behaviors in both domains induced increased activations in the anterior medial prefrontal cortex (MPFC, BA9/10)/ventral anterior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 84 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…Also consistent with studies of economic decision making (Knutson et al, 2005;Tom et al, 2007), we found that BOLD signal in regions of central insula, dorsal striatum, and anterior and posterior cingulate cortices was sensitive to the magnitude of the potential loss/gain associated with decision options. Also consistent with previous studies of decision making (particularly ones involving the assessment of risk) (Paulus et al, 2003;Qin and Han, 2009), we found that BOLD signal in the left posterior insula was sensitive to the probability of loss/gain associated with decision options. Among the key limitations of the present paradigm is that valence at encoding cannot be determined based on the task alone.…”
Section: Neuronsupporting
confidence: 91%
“…Also consistent with studies of economic decision making (Knutson et al, 2005;Tom et al, 2007), we found that BOLD signal in regions of central insula, dorsal striatum, and anterior and posterior cingulate cortices was sensitive to the magnitude of the potential loss/gain associated with decision options. Also consistent with previous studies of decision making (particularly ones involving the assessment of risk) (Paulus et al, 2003;Qin and Han, 2009), we found that BOLD signal in the left posterior insula was sensitive to the probability of loss/gain associated with decision options. Among the key limitations of the present paradigm is that valence at encoding cannot be determined based on the task alone.…”
Section: Neuronsupporting
confidence: 91%
“…Furthermore, there is well established literature showing that hazardous/risky information is processed differently from safe information in the brain [ 24 31 ]. Hazardous/risky information, in contrast to safe information, has been found to elicit stronger activations in medial prefrontal cortex [ 24 , 25 , 31 ], anterior insula[ 29 , 31 ], ventral anterior cingulate cortex and posterior cingulate cortex[ 24 26 , 29 ], etc. Meanwhile, ERPs studies suggested that hazardous/risky information evoke larger P200 and LPP amplitudes than safe information [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precuneus has been tightly linked to evidence accumulation in decision making situations [52] , in particular in unpredictable situations [53] . Accordingly, the precuneus is also reported to be active during risky decisions [54] , [55] and the identification of risk [56] . With respect to the present investigation active NAcc-DBS seems to increase activation in cortical areas which are necessary for identifying situations that are (potentially) disadvantageous.…”
Section: Discussionmentioning
confidence: 99%